2016
DOI: 10.1016/j.nlm.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in discriminating between cues predicting threat and safety

Abstract: HighlightsWe investigated sex differences in auditory fear discrimination in rats.Males that received extended discrimination training showed fear discrimination.Females discriminated after limited training and generalized after extended training.Generalization with extended training in females involved impaired safety signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 49 publications
13
54
1
Order By: Relevance
“…First, our experiments only used male rats. Several studies have reported sex differences in danger-safety discrimination (Day et al, 2016;Foilb et al, 2018;Greiner et al, 2019). We find only modest sex differences in our fear procedure (Walker et al, 2018;Walker et al, 2019), suggesting similar neural circuits may be utilized across sexes.…”
Section: Discussionsupporting
confidence: 56%
“…First, our experiments only used male rats. Several studies have reported sex differences in danger-safety discrimination (Day et al, 2016;Foilb et al, 2018;Greiner et al, 2019). We find only modest sex differences in our fear procedure (Walker et al, 2018;Walker et al, 2019), suggesting similar neural circuits may be utilized across sexes.…”
Section: Discussionsupporting
confidence: 56%
“…Considering these findings in interpreting our current results, it is possible that males experienced more aversive motivation after re-exposure in our AAT, and this could explain why (1) a subset of males exhibited learned helplessness-like behavior, and (2) the males in the full task were more motivated to avoid the shock on all avoidance trials. The second hypothesis is consistent with the findings of Day et al, who showed that females demonstrate greater discrimination than males after limited training, and generalization after extended training on a fear discrimination task (Day, Reed, & Stevenson, 2016) . Together with our current findings, these results are consistent with the idea that women's vulnerability to anxiety disorders stems from accumulating experience of aversive contexts Finally, we investigated potential sex differences in reward-motivated actions within a context of high cognitive load, requiring flexible shifts between dynamic cue-action-reward contingencies.…”
Section: The Study Of Sex Differences Relevant To Psychiatric Diseasesupporting
confidence: 90%
“…The inability to effectively inhibit fear is a phenotype of PTSD and is involved in its neurocircuitry and clinical symptoms (Jovanovic, Kazama, Bachevalier, & Davis, ; Jovanovic & Norrholm, ). Generally, fear inhibition includes three processes: (a) fear extinction refers to learning previous threat cues are no longer dangerous (Milad & Quirk, ); (b) safety learning occurs when one learns that environmental stimuli predict safety (Marshall, Acheson, Risbrough, Straus, & Drummond, ); and (c) fear–safety discrimination is the process of distinguishing between “threat” and “safety” cues when simultaneously presented (Day, Reed, & Stevenson, ). Animal models of fear inhibition have been developed to advance understanding of these phenomena (Bowers & Ressler, ; Pollak, Monje, & Lubec, ).…”
Section: Introductionmentioning
confidence: 99%